KETERGABUNGAN PENDIDIKAN KARAKTER DAN POSITIVE FEEDBACK DALAM PEMBELAJARAN BAHASA INGGRIS - Muksin, Muh. Arief; Sastrawati, Ika (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
The research aimed to investigate the devoloptmen of students’ positive character in collaborating character education and positive feedback in teaching English at Sekolah Islam Athirah Makassar. The research was descrictive kualitative which the data was getting from the true situation in the field. It can be designed discussing method, following up, data analysis, and colleration. There were there forms used to get the data like observation, interview (students and teacher), and questionnaire. The research result showed there were eight characters used that school to bulid Islamic school in Sekolah Islam Athirah, they were spiritual; discipline, honest, responsibility, tolerance, politeness, and confidence. The collaboration charcter education and positive feedback used more than in the classroom. In teaching English case, teacher usually used explicit correction and metalinguistic feedback. It used because generally students more writing than speaking in the class. All kinds of feedback used in teaching but explicit correction and metalinguistic feedback are more than other.